Hemorrhagic Spinal Schwannoma in Thoracolumbar Area with Total Paraplegia - Ahmad Jabir Rahyussalim; Rizky Priambodo Wisnubaroto; Tri Kurniawati; Alfariq Senja Belantara Latsarizul; Nuryati Chairani (Case Reports in Medicine)
Hemorrhagic schwannoma in the medulla spinalis is a rare occurrence. It is a variant of the slow-growing nerve sheath tumor that usually has subtle clinical symptoms. Injury to the spinal schwannoma that was previously suspected by spinal manipulations may accelerate the progression of symptoms and cause an acute presentation of paraplegia. We report a case of a patient that was suspected of an intradural tumor with paraparesis that initially refused treatment. Spinal manipulation procedures were performed outside of the hospital setting with subsequent advancement of paraparesis. A surgical intervention was performed, which found that the tumor mass has grown along with hemorrhage within the schwannoma. The bleeding within the mass may have caused the acute paraplegia that is rarely reported. The patient had a fair improvement on her lower motor extremity function from 1‐2 to 3‐4 out of 5 at six‐month follow-up.